Structural modification aimed for improving solubility of lead compounds in early phase drug discovery - Das B.; Baidya A.T.K.; Mathew A.T.; Yadav A.K.; Kumar R. (My University, 2025)
Many lead compounds fail to reach clinical trials despite being potent because of low bioavailability attributed to their insufficient solubility making solubility a primary and crucial factor in early phase drug discovery. Solubility improvement of poorly soluble lead compounds without losing potency is a challenging task for the medicinal chemist in a drug discovery setup. Solubility is an important factor not only to dissipate or liquefy a substance but also to attain an optimal concentration of drug in systemic circulation required for the desired therapeutic effect. It has been estimated that more than forty percent of newly developed molecules are practically insoluble in water. Molecules with poor solubility not only cause difficulty for in vitro and in vivo assays but also add significant burdens to drug development in the form of longer time taken and increased cost to optimize the solubility. To tackle this problem, different techniques are being used such as physical, chemical, and miscellaneous methods to enhance solubility. Among them, the medicinal chemistry approach focussed on structural modification is a versatile and unique approach in way that it can also improve other pharmacokinetic/physicochemical parameters simultaneously. In this review, we have begun with brief introduction of solubility and its role followed by recent successful examples of different structural modification tactics reported in the literature including synthesis of prodrugs, hydrophilic and ionizable group insertion, addition & removal of hydrogen bonding, bioisosterism, disruption of molecular symmetry and planarity. Moreover, we have included a section on the obstacles in the solubility optimization and also summarised different in silico tools with potential application in solubility prediction. Overall, this review encompasses various successfully used solubility optimization examples using structure modification. © 2022 Elsevier Ltd